Psychopathological symptoms, personality, and epistemic stances in individuals with myocardial infarction: an empirical investigation - Cruciani, Gianluca; Liotti, Marianna; Tanzilli, Annalisa; Lo Buglio, Gabriele; Guarino, Davide; Carone, Nicola; Casali, Matteo; Galli, Federica; Lingiardi, Vittorio (Frontiers in Psychology, 2025)
IntroductionMyocardial infarction (MI) is a major cause of mortality worldwide. Psychopathological symptoms play a bidirectional role in MI prognosis, both increasing cardiovascular risk and being exacerbated by cardiac events, leading to further complications. Personality impairments and disruptions in epistemic trust—the ability to assess social communications as trustworthy and relevant—strongly affect psychopathology levels and may worsen MI clinical outcomes by impeding health behaviors and treatment adherence. This is the first study examining the interplay between psychopathological symptoms, personality dysfunction, and epistemic dimensions in MI patients compared to healthy controls.MethodsA sample of 67 MI patients and 80 age- and gender-matched healthy controls completed self-report measures to assess levels of general psychopathology (DSM−5 self-rated Level 1 Cross-Cutting Symptom Measure), personality functioning (Personality Inventory for DSM-5 Short Form), and epistemic stances (Epistemic Trust, Mistrust, and Credulity Questionnaire). Multivariate analyses were used to compare the groups, while correlations and moderation models were employed to evaluate associations among variables within the MI group.ResultsMI patients showed significantly higher psychopathological symptoms, more severe personality impairments, and greater epistemic mistrust than controls. Within the MI group, psychopathological symptoms were associated with specific maladaptive personality traits (especially, negative affectivity) and epistemic mistrust and credulity. The relationship between worse personality functioning and severe psychopathological symptoms was moderated by epistemic mistrust.DiscussionThe study emphasizes the importance of addressing psychopathology and epistemic disruptions in clinical settings to improve the treatment's adherence and recovery. The development of targeted interventions to mitigate psychological vulnerabilities in MI patients is recommended.